Analysis Control Of Inventory Of Non Subsidy Fertilizer Merchandise With Economic Order Quantity (EOQ) Method In CV. Dohar Agro Mandiri - Ferza Dwianda Afrimarsa; Neri Susanti; Tito Irwanto (Penerbit Jurnal Indonesia, 2022)
Economic Order Quantity (EOQ) is a mathematical model that determines the number of items that must be ordered to meet the projected demand, with minimized inventory costs. The types of costs to run the business cycle are storage costs and ordering costs. The purpose of this research is to analyze